2021
DOI: 10.1155/2021/8906561
|View full text |Cite
|
Sign up to set email alerts
|

Cooling and Sterile Inflammation in an Oxygen-Glucose-Deprivation/Reperfusion Injury Model in BV-2 Microglia

Abstract: Objective. Cold-inducible RNA-binding protein (CIRBP) has been shown to be involved not only in cooling-induced cellular protection but also as a mediator of sterile inflammation, a critical mechanism of the innate immune response in ischemia/reperfusion (I/R) injury. The role of microglia and its activation in cerebral I/R injury warrants further investigation as both detrimental and regenerative properties have been described. Therefore, we investigated the effects of cooling, specifically viability, activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…In fact, L-NAME has been widely employed to inhibit eNOS activity in various cellular studies [ 52 , 53 , 54 ]. Although it has been reported that iNOS expression and cellular death can be observed in endothelial cells (ECs) 4 h after OGD [ 55 ], iNOS levels return to normal levels 25 h after OGD [ 51 , 56 ]. We discovered in the present study that endostatin levels were increased by L-NAME at 48 h following OGD, suggesting that L-NAME modulates endostatin in an iNOS-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, L-NAME has been widely employed to inhibit eNOS activity in various cellular studies [ 52 , 53 , 54 ]. Although it has been reported that iNOS expression and cellular death can be observed in endothelial cells (ECs) 4 h after OGD [ 55 ], iNOS levels return to normal levels 25 h after OGD [ 51 , 56 ]. We discovered in the present study that endostatin levels were increased by L-NAME at 48 h following OGD, suggesting that L-NAME modulates endostatin in an iNOS-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The cells with proper density should suck up the original culture medium, pre‐cool the PBS cells twice, then add 2 mL of glycose‐free culture medium (without serum) and put them into a mix gas incubator (37°C, 1% O 2 + 94% N 2 + 5% CO 2 ) for oxygen–glucose deprivation (OGD). After 6 h of OGD operation, discard the original culture medium and PBS cells twice, add 2 mL of high glucose culture medium (without serum) and put them into a normal incubator (37°C, 5% CO 2 ) for reoxygenation treatment to simulate reperfusion (Lücht et al., 2021; Xian et al., 2021). BV2 cells were infected with lentiviral particles, contained short hairpin (sh)RNA and exogenous over‐expression (OE) RNA according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“… 97 A large number of inflammatory markers have been shown to be inhibited by cooling. 80 , 86 , 93 , 117 , 118 , 119 , 123 , 124 , 125 , 126 , 127 , 128 , 129 Downregulatory effects are seen on the expression of MMP-9 mRNA and upregulating effects on the expression of chemokine (C-X-C motif) ligand 13 (CXCL13), lipopolysaccharide binding protein, and chemokine (C-C motif) ligand 6 (CCL6) and chemokine (C-C motif) ligand 24 (CCL24). These molecules have important functions in B-cell maturation, reduction in endotoxin load and improved bacterial opsonization, keratinocyte proliferation, and collagen synthesis and deposition by fibroblasts.…”
Section: Delayed Effects and The Influence Of Coolingmentioning
confidence: 99%